Persepsi Masyarakat dalam Kebijakan Merger Bank Syariah Indonesia Studi Kasus Kabupaten - Mustofa, Muhammad Ali; Jannah, Mulyani Fatekhatul; Zaman, Malik Ibnu (Jurnal Ekonomika dan Bisnis Islam, 2022)
A low share of the Islamic banking market of 6.01% has led the government to take the initiative to conduct a Syariah bank merger to increase the growth and development of Indonesian Islamic banking as well as drive perceptions in the public that can encourage potential advancement in banking sharia in Indonesia that has not been achieved. This study aims to analyze the perceptions of the people in Tegal Regency towards the BSI merger from the aspects of potential, preference, and religiosity. This research used a type of descriptive quantitative research with an explanatory research approach. The population in this study was all people in Tegal Regency. The sampling technique was carried out using the convenience sampling technique through primary data from as many as 100 respondents. Methods of data analysis using multiple linear regression analysis. The t-test results showed that the potential variable partially had no significant effect on perceptions in the BSI merger, while preference and religiosity partially had a significant effect on public perceptions. The results of the F test show that potential, preference, and religiosity simultaneously influence people’s perceptions. From the results of the study, it can be concluded that the hypothesis is accepted.